2020
DOI: 10.1088/1757-899x/869/3/032011
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation of Nano Silica Effects to High Performance Concrete Strength in Early Age

Abstract: Nano silicate SiO2 (NS) in the high-performance concrete (HPC) mixture is becoming great interest because it improves the mechanical properties of concrete. As the ultra-fine SiO2 particles with a very high ratio of surface area to mass, NS can tightening the structure and produces better quality gel products and thus concrete strength increases. However, the optimal rate of NS in high-performance concrete has not been investigated. This study experimentally evaluates the influence of NS on compressive strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…For instance, the flexural and compressive strengths of concrete grow considerably with the NS ratio from 0 to 1.5%, reaching 19.19% and 20.97%, respectively. Certain studies [50][51][52][53][54][55] also confirmed the tendency of this increase in strength. A previous study reported by Naji Givi et al [51] found that concrete with an NS component of 1.0 ÷ 1.5% has a higher bending strength than control concrete.…”
Section: Compressive Strength and Flexural Strengths At Early Curing Agementioning
confidence: 64%
“…For instance, the flexural and compressive strengths of concrete grow considerably with the NS ratio from 0 to 1.5%, reaching 19.19% and 20.97%, respectively. Certain studies [50][51][52][53][54][55] also confirmed the tendency of this increase in strength. A previous study reported by Naji Givi et al [51] found that concrete with an NS component of 1.0 ÷ 1.5% has a higher bending strength than control concrete.…”
Section: Compressive Strength and Flexural Strengths At Early Curing Agementioning
confidence: 64%
“…Steel fber concrete is used quite commonly because they have increased load capacity, reduced the number of cracks, increased construction life, and have good impact resistance. A few studies on nanoconcrete with steel fbers (SFs) looked into the efects of concrete aggregation on increasing concrete tensile strength [1], the enhanced plasticity of concrete with SFs [2], and an observation design was also carried out to consider nanosilica efects on HPC strength at an early age [3], the fracture features of SFs' reinforced concrete beams [4]. A number of scholars have started referring to a series of studies on the RC beams with and without SFs; these studies have constructed a stress strain of the reinforced concrete (RC) beams with SF contents in concrete of 0%, 4%, and 8% by volume.…”
Section: Introductionmentioning
confidence: 99%